Quantitative Trait Loci Mapping Analysis for Cold Tolerance Under Cold Stress and Brassinosteroid-Combined Cold Treatment at Germination and Bud Burst Stages in Rice - Guo, Zhifu; Wang, Haotian; Yao, Jialu; Cheng, Yishan; Zhang, Wenzhong; Xu, Zhengjin; Li, Maomao; Huang, Jing; Zhao, Minghui (Frontiers in Plant Science, 2022)
Low temperature is one of the major abiotic stresses limiting seed germination and early seedling growth in rice. Brassinosteroid (BR) application can improve cold tolerance in rice. However, the regulatory relationship between cold tolerance and BR in rice remains undefined. Here, we constructed a population of 140 backcross recombinant inbred lines (BRILs) derived from a cross between a wild rice (Dongxiang wild rice, DXWR) and a super rice (SN265). The low-temperature germination rate (LTG), survival rate (SR), plant height (PH), and first leaf length (FLL) were used as indices for assessing cold tolerance under cold stress and BR-combined cold treatment at seed germination and bud burst stages. A high-resolution SNP genetic map, covering 1,145 bin markers with a distance of 3188.33 cM onto 12 chromosomes, was constructed using the GBS technique. A total of 73 QTLs were detected, of which 49 QTLs were identified under cold stress and 24 QTLs under BR-combined cold treatment. Among these, intervals of 30 QTLs were pairwise coincident under cold stress and BR-combined cold treatment, as well as different traits including SR and FLL, and PH and FLL, respectively. A total of 14 candidate genes related to cold tolerance or the BR signaling pathway, such as CBF/DREB (LOC_Os08g43200), bHLH (LOC_Os07g08440 and LOC_Os07g08440), WRKY (LOC_Os06g30860), MYB (LOC_Os01g62410 and LOC_Os05g51160), and BRI1-associated receptor kinase 1 precursor (LOC_Os06g16300), were located. Among these, the transcript levels of 10 candidate genes were identified under cold stress and BR-combined cold treatment by qRT-PCR. These findings provided an important basis for further mining the genes related to cold tolerance or the BR signaling pathway and understanding the molecular mechanisms of cold tolerance in rice.